The Meaning Of Diasporic Identity: A Case Of Indonesian Community Overseas - Oktafiani, Irin (Journal of Indonesian Social Sciences and Humanities, 2019)
This paper argues that the term of the diaspora in Indonesia has been transformed and simplified from the general diaspora concept and its conceptual meaning is not enough to define the Indonesian diaspora. The Indonesian government have already made a clear characteristic of Indonesian diaspora through the Presidential Regulation No. 76 of 2017, it is stated implicitly that Indonesian diaspora is whoever living abroad, despite they only live there for a short period. Regardless of what the Indonesian government has done to define the meaning of the diaspora, the definition is not enough to explain about Indonesian diaspora. By any conditions, the Indonesian government could not neglect the history of some Indonesian political refugees in 1965 or 1998 since there was a painful history left behind and it is unsure whether they want to recognize themselves again as Indonesia. On the other hand, the second generation or more of Indonesian who already got another country citizenship, cannot be guaranteed to have a sense of belonging with Indonesia and want to recognize that they have Indonesian descent. This paper will elucidate what really matters in the term of Indonesian diaspora in the sense of belonging and the confession that they are being attached to Indonesia.